Sistem Informasi Recruitment Karyawan Pada Human Resouce Departement Berbasis Web Metode Analytic Hierarchy Process (AHP) - Apriliyani, Awanda; Imam Agung, Achmad (Inovate, 2023)
Recruitment application PT. Pou Yuen Indonesia is an application that is useful for receiving and selecting job application files sent by applicants to companies. This system can make it easier for HRD to select employees and speed up the selection results. The selection process in this system uses a hierarchical analytical process calculation method, where the output is in the form of file rankings assessed from several criteria including education, expertise and completeness. In this system research, several stages are carried out, namely data collection, system requirements analysis, system analysis and design, system development, and ends with testing. With a web-based recruitment system, the recruitment process becomes effective and efficient. Keywords: Recruitment, Human Resources Department, Analytical Hierarchy Process, Website